Vinaññʻʺ dhammakaṃ cī raṅʻ thuṃʺ myāʺ - Kraññʻ Phe, Ūʺ (Praññʻ thoṅʻ cu Chuirhayʻlacʻ Sammata Mranʻ mā Nuiṅʻ ṅaṃ toʻ, Sāsanā reʺ Ūʺ cīʺ Ṭhāna, 1982)
Rulings of the courts presided by Buddhist monastics in Burma, 1853-1953, applying rules from Vinayapitaka, Buddhist canon.